Students’ Coursework Evaluation System (SCES) / Deng Wei Ling - Deng , Wei Ling (2001)
Today, information technology has pervaded into almost every industry in the country. Institutions and Universities today are moving towards paperless environment and computerized their current systems to ensure smoother operations in the daily running operation. Students' Coursework Evaluation is introduced as to give a new impulse for the Institution and Universities to gain competitive advantage. Students' Coursework Evaluation System is designed to enable students to access courses information and submit their assignments as well as sitting for online test or quizzes. They can also view the grading of coursework through the World Wide Web. The second purposes of SCES arc to enable the lecturers to mark the students' coursework and evaluating the students’ performance. SCES is able to provide a comprehensive Web-Based coursework environment for the education industry. This report introduces the project and provides a description on the topics studied and researched during the literature review. It also describes the software development process that occurred in the project with details on the s system analysis and design. This database system supports the fundamental database operations such as data insertion and data retrieval for administrator, student and lecturer. It is hope that the major problems faced by the current system in one organization can be solved through this system.